(iii) Temporary skeletal stabilization in major trauma. Issue 6 (December 2015) - Taylor, D.M.; Tebby, J.M.; Foster, P.A.; Harwood, P.J.
Abstract: Pelvic and long bone fractures are common amongst major trauma patients. Rapid and safe skeletal stabilization is an important step in the early management of these patients, as part of systemic damage control as well as local fracture and soft tissue management. A clear understanding of the anatomy and biomechanics is required to carry out safe pin insertion and stable external fixator construction.